2016
DOI: 10.3390/cosmetics3010006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cosmetic Lotions on Nanoparticle Penetration through ex Vivo C57BL/6 Hairless Mouse and Human Skin: A Comparison Study

Abstract: Understanding the interactions of nanoparticles (NPs) with skin is important from a consumer and occupational health and safety perspective, as well as for the design of effective NP-based transdermal therapeutics. Despite intense efforts to elucidate the conditions that permit NP penetration, there remains a lack of translatable results from animal models to human skin. The objectives of this study are to investigate the impact of common skin lotions on NP penetration and to quantify penetration differences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 60 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Their findings suggest that certain ingredients (e.g., urea, glycerol, and α-hydroxyl acids) found in common commercial skin care lotions can enhance NP penetration into the skin. 145 In addition, several chemical penetration enhancers have shown their potential to support skin penetration by nanoparticles. 146 Kuo et al illustrated the differences between oleic acid, ethanol, and oleic acid−ethanol enhancers for the transport of zinc oxide nanoparticles.…”
Section: Impact Of Nanoplastics On Human Healthmentioning
confidence: 99%
“…Their findings suggest that certain ingredients (e.g., urea, glycerol, and α-hydroxyl acids) found in common commercial skin care lotions can enhance NP penetration into the skin. 145 In addition, several chemical penetration enhancers have shown their potential to support skin penetration by nanoparticles. 146 Kuo et al illustrated the differences between oleic acid, ethanol, and oleic acid−ethanol enhancers for the transport of zinc oxide nanoparticles.…”
Section: Impact Of Nanoplastics On Human Healthmentioning
confidence: 99%
“…Mechanisms for urea‐dependent skin permeability enhancement were previously discussed; for example, in the works Albèr et al and Björklund et al described the enhancement of skin permeability mediated by urea, as effect of ultrastructural changes . Furthermore, Jatana et al suggested that commonly used active ingredients, such as urea and glycerol, could highly affect the skin penetration of particulates, and thus, it could possibly results in the cutaneous deposition of water‐soluble macromolecules up to a size of few nanometres . According to these studies, systemic permeation of the macromolecular drug is unlikely and the chemistry structure of the siRNA used does not make it particularly suitable as a long circulating system.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown here that both vehicles and branded skin care products can induce severe adverse reactions in normal mouse skin, which is much thinner (∼ 15 μm) (56) and more permeable (20,21) than human skin (∼ 75-96 μm) (57), making it more susceptible to stimuli than normal human skin. Therefore, depending on regulatory issues related to the testing of such products in animals, mouse skin could serve as a useful model with which to evaluate the safety of over-the-counter skin care products and cosmetics.…”
Section: Discussionmentioning
confidence: 99%
“…Although skin care products can cause few or no adverse reactions in normal human skin, they could still provoke cutaneous symptoms in subjects with sensitive skin. Accordingly, in the present study, we assessed the impact of several vehicles and branded skin care products on epidermal functions in normal mice, whose skin is more permeable than human skin . This model could serve as a useful analogue of sensitive skin in humans.…”
mentioning
confidence: 99%